Comparative Analysis of Post Office Service Quality with JNE in Purworejo - Niko Dwi Haryanto (Master of Management Diponegoro University, 2022)
The hardest thing for a company to do is to assess the quality of its service with competitors in the same sector, most companies only assess the quality of service to their own customers, and it makes it difficult for companies to grow and develop, especially for the post office in the midst of many other expedition services and one of them is JNE. The scope of the research is Purworejo, Central Java. The number of samples is 110 people consisting of 55 Pos and JNE customers. The sampling technique used was accidental sampling. The data testing technique uses validity and reliability tests. The analysis technique used in this study is carried out using the Customer Zone of Tolerance Quality (CZSQ) which is integrated with Importance Performance Analysis (IPA) and becomes CZSQ-IPA (CZIPA). The results showed that Pos with the CZIPA matrix method, there were 3 attributes in quadrant 1, 4 attributes in quadrant 2, 5 attributes in quadrant 3 and 6 attributes in quadrant 4. The conclusions in this study indicate that there are 2 main priorities for improvement, namely responses to suggestions and complaints from customers with d value of -3.04 and the ability of employees to solve customer problems with a d value of -2.14.